Веселые рассказы для детей - Зощенко Михаил Михайлович (Любимая книжка, 2018)
Экземпляры: (20190603) / Инвентарный номер: 50391 / Цена: 200.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: З-88 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-44